Evaluasi Sistem Reward dan Punishmen dalam Manajemen Kinerja Karyawan-Karyawan Telkomsel Maumere - Maria Mektildis; Elisabeth Mitan; Bernadetha Dua Bregun; Maria Silvana Mariabel Carcia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to evaluate the effectiveness of the reward and punishment system in employee performance management at Telkomsel Maumere, as well as to provide recommendations for improvements that can be implemented to enhance employee performance and job satisfaction.